PRECISION ENGINEERING OF "IIK-D1" SERIES CORROSION INHIBITORS: PRODUCTION INSIGHTS - Davlyatova Zulfiya Muratovna; Polvonov Khurshid Madaminovich (European Science Publishing, 2023)
The article notes that the technology for the production of corrosion inhibitors of the "IIK-D1" series was introduced in the joint venture "Elektrokimyozavod", which made it possible to develop an energy-saving technology for producing corrosion inhibitors based on secondary products of the fat and oil industry based on acid catalysts, which eventually cost 1.5-1.8 times cheaper. The technology of mass production of corrosion inhibitors was introduced in the joint venture “Elektrokimyozavod”, the result allowed to obtain a corrosion inhibitor soluble in hydrocarbons based on imidozoline with a degree of protection of oil production and processing plants 93%.
Keywords: inhibitor, corrosion, technology, Fat and oil industry, hydrocarbon, imidazoline.